Redesain MOOC Teknologi Kinerja Berbasis ADDIE: Validasi Kelayakan Pedagogis dan Media - Aprilia Ghifari Faizatun Ni'mah; Cahyani , Izza Alfina; Aeni, Lisda Hilya (Universitas Negeri Jakarta, 2025)
The growing demand for flexible, high-quality learning experiences has positioned MOOCs as a strategic response to postgraduate education needs. However, many MOOCs remain limited in interactivity and contextual relevance. This study presents a redesign of a MOOC for a graduate-level Human Performance Technology (HPT) course, developed using the first three stages of the ADDIE model: analysis, design, and development. The process integrated structured content, communicative media, and learner-centered design principles grounded in objectivist-individual and humanistic learning theories. Feasibility was evaluated through expert validation and user trials using a weighted Likert-scale instrument. Results indicated high feasibility scores: 92.17% from content experts, 75.00% from media experts, and 96.56% from users. While the MOOC was deemed pedagogically and technically sound, minor revisions were recommended. This study reinforces the AECT (2004) definition of educational technology as an ethical practice of facilitating learning and improving performance, and contributes to the advancement of theory-driven, competency-based MOOC design.